Words without vowels: phonetic and phonological evidence from Tashlhiyt Berber - Ridouane, Rachid (ZAS Papers in Linguistics, 2002)
This article deals with the Tashlhiyt dialect of Berber (henceforth TB) spoken in the southern part of Morocco. In TB, words may consist entirely of consonants without vowels and sometimes of only voiceless obstruents, e.g. tft#tstt "you rolled it (fem)". In this study we have carried out acoustic, video-endoscopic and phonological analyses to answer the following question: is schwa, which may function as syllabic, a segment at the level of phonetic representations in TB? Video-endoscopic films were made of one male native speaker of TB, producing a list of forms consisting entirely of voiceless obstruents. The same list was produced by 7 male native speakers of TB for the acoustic analysis. The phonological analysis is based on the behaviour of vowels with respect to the phonological rule of assibilation. This study shows the absence of schwa vowels in forms consisting of voiceless obstruents.